Synthesis of two novel [18F]fluorobenzene-containing radiotracers via spirocyclic iodonium ylides and positron emission tomography imaging of translocator protein (18 kDa) in ischemic brain. Issue 37 (12th September 2018) - Fujinaga, Masayuki; Kumata, Katsushi; Zhang, Yiding; Hatori, Akiko; Yamasaki, Tomoteru; Mori, Wakana; Ohkubo, Takayuki; Xie, Lin; Nengaki, Nobuki; Zhang, Ming-Rong
Abstract : A new radiotracer for imaging TSPO: K i, 0.70 nM and no radiolabeled metabolite in the brain. Abstract : Two novel radiotracers, namely, N -(4-[ 18 F]fluorobenzyl)- N -methyl-2-(7-methyl-8-oxo-2-phenyl-7, 8-dihydro-9 H -purin-9-yl)acetamide ([ 18 F]5 ) and 2-(5-(4-[ 18 F]fluorophenyl)-2-oxobenzo[ d ]oxazol-3(2 H )-yl)- N -methyl- N -phenylacetamide ([ 18 F]6 ), were developed for positron emission tomography (PET) imaging of translocator protein (18 kDa) (TSPO) in ischemic brain in this study. The two radiotracers with a [ 18 F]fluorobenzene ring were derived from the corresponding [ 18 F]fluoroethyl tracers [ 18 F]7 and [ 18 F]8 which underwent [ 18 F]defluoroethylation in vivo easily. [ 18 F]5 or [ 18 F]6 was synthesized by the radiofluorination of the spirocyclic iodonium ylide precursor10 or17 with [ 18 F]F − in 23 ± 10% ( n = 7) or 56 ± 9% ( n = 7) radiochemical yields (decay-corrected, based on [ 18 F]F − ). [ 18 F]5 and [ 18 F]6 showed high in vitro binding affinities ( K i = 0.70 nM and 5.9 nM) for TSPO and moderate lipophilicities (log  D = 2.9 and 3.4). Low uptake of radioactivity for both radiotracers was observed in mouse bones. Metabolite analysis showed that the in vivo stability of [ 18 F]5 and [ 18 F]6 was improved in comparison to the parent radiotracers [ 18 F]7 and [ 18 F]8 . In particular, no radiolabelled metabolite of [ 18 F]5 was found in the mouse brains at 60 min after the radiotracer injection. PET studies with [ 18 F]5 on ischemic rat brains revealed a higher binding potential (BPND = 3.42) and maximum uptake ratio (4.49) between the ipsilateral and contralateral sides. Thus, [ 18 F]5 was shown to be a useful PET radiotracer for visualizing TSPO in neuroinflammation models.